Phagocytic Integrins: Activation and Signaling - Torres-Gomez, Alvaro; Cabañas, Carlos; Lafuente, Esther M. (Frontiers in Immunology, 2020)
Phagocytic integrins are endowed with ability to engulf and dispose of particles of different nature. Evolutionarily conserved from worms to humans, they are involved in pathogen elimination, apoptotic and tumoral cell clearance. Research in the field of integrin-mediated phagocytosis has shed light on the molecular events controlling integrin activation and their effector functions. However, there are still some aspects of regulation the phagocytic process that need to be clarified. Here, we revise the molecular events controlling phagocytic integrin activation and the downstream signaling driving particle engulfment, with special focus on αMβ2/CR3, αXβ2/CR4 and a brief mention of αV5/αV3 integrins.